Development of a 3D Pipe Robot for Smart Sensing and Inspection Using 3D Printing Technology. Issue 3 (3rd July 2017) - Chang, Wen-Chung; Huang, Yang-Cheng; Chang, Pei-Ying
Abstract: This 3D pipe inspection robot is capable of conducting fully autonomous pipe inspection, transmitting measured data to the monitoring end by wireless communication, drawing a 3D pipe routing map in real time, and detecting pipe anomalies. The robot is both lightweight and inexpensive because it is constructed by 3D printing. The main functions of the robot include calculating the robot posture using the measurements from the accelerometer and gyroscope module, drawing a 3D pipe routing map in real time, deciding the degree of contraction from pressure sensor module readings to detect abnormal expansion or contraction, and locating potential hazards in the pipe. The robot described in this paper is different from others in many ways. The freely extendable and contractible body structure allows the robot to easily adapt to pipes of various diameters. The wireless IP camera onboard transmits real-time videos and assists operators in looking for signs of damage or anomalies. This robot is practical and can be used for the inspection of damaged pipes, redrawing 3D pipe routing maps, and assisting in the regular maintenance of pipes underground or located within buildings, and may also be of use in rescue work and disasters, etc. Abstract :